Prevalência de insuficiência/deficiência de vitamina D e sua relação com marcadores inflamatórios e de estresse oxidativo em pacientes com psoríase - Silva, Maria Thayná Bernardo Ferreira da (2024)
Psoriasis is a chronic inflammatory skin disease and its pathogenesis is associated with dysregulation of the immune system and the presence of oxidative stress. This clinical condition was associated with low levels of vitamin D, a nutrient capable of modulating immune responses and reducing the expression of inflammatory cytokines. However, the understanding of the relationship between vitamin D and inflammatory and oxidative stress markers in psoriasis is not yet consolidated. The general objective of this study was to determine the prevalence of vitamin D insufficiency/deficiency in patients with psoriasis from a referral center in Paraíba and to relate serum levels of 25-hydroxyvitamin D (25(OH)D) with inflammatory and oxidative stress markers. This cross-sectional study was conducted with 146 patients from a reference center for the treatment of psoriasis in Paraíba/Brazil, recruited between November 2022 and August 2023. Patients aged between 20 and 59 years, of both sexes and with a clinical diagnosis of psoriasis, were included. The severity of psoriasis was assessed by the Dermatology Life Quality of Index (DLQI). Clinical, lifestyle, anthropometric and food consumption data were collected, and laboratory analyses of 25(OH)D, parathyroid hormone, total calcium, inflammatory markers: ultrasensitive C-Reactive Protein (hs-CRP), Alpha-1-Acid Glycoprotein (AGP), Tumor Necrosis Factor Alpha (TNF-α), Interferon Gamma (IFN-γ) and Interleukins 2, 6 and 10 (IL-2, IL-6, IL-10) were performed, in addition to oxidative stress markers: Malondialdehyde (MDA) and Total Antioxidant Capacity (TAC). For the statistical analyses, the sample was divided into two groups, according to the 25(OH)D classification: sufficiency and insufficiency/disability. The software used was the IBM® SPSS Statistics 21 and the results with a p-value <0.05 were considered significant. Among the participants, 56.8% had sufficient serum levels of 25(OH)D and 43.1% had inadequate levels, 39% with insufficiency and 4.1% with deficiency. The most frequent skin phototypes were II (fair skin) (24.7%), III (less light skin) (27.4%) and IV (light brown skin) (24.7%). A significant association was observed between the classification of 25(OH)D and sun exposure (p=0.007). Vitamin D intake did not differ between the groups. IL-2 and IL-6 were significantly higher in the insufficiency/deficiency group (p=0.015 and p=0.017, respectively). The mean MDA was significantly higher in the sufficiency group (p=0.005), while the TAC did not differ between the groups (p=0.917). Significant inverse correlations were observed between 25(OH)D and IL-2, IL-6 and DLQI (p<0.05), and a positive correlation with MDA (p=0.038). The other inflammatory and oxidative stress markers did not show a correlation with 25(OH)D. The univariate linear regression model showed that body mass index, waist circumference, IL-2, IL-6 and MDA were independent predictors of 25(OH)D. After the insertion of adjustment variables, body mass index, waist circumference, and IL-6 remained as predictor variables of 25(OH)D. This study revealed a high prevalence of vitamin D insufficiency in patients with psoriasis. In addition, these findings suggest that low vitamin D levels are associated with more severe inflammation, excess weight, and reduced quality of life in this population.